Influencia De Un Programa De Entrenamiento De Parkour En El Desarrollo De La Potencia De Piernas En Los Practicantes Del Grupo Urban Ninjas Armenia (2014)
In this research, eight practitioners-athletes were chosen between 16 and 18 years old, with more than one (1) year of practice within the group of Parkour Urban Ninjas Armenia four of which were part of the experimental group and four control group, each will be evaluated his leg power through a pre-test (horizontal standing jump with feet together). We apply a fitness program to the experimental group in order to improve leg power, explosive strength and rapid strength through exercises or sessions lasting an hour and a half and a practice three times a week for three months while the control group trained without the stimulus of the training program designed. Upon completion of the training sessions were evaluated leg power to the experimental group and control group with a post-test equal to the pre-test (horizontal standing jump with feet together). The data obtained from the results of tests suggest that physical training program based on Parkour had no statistically significant difference between the pre-test and post-test in the experimental group to increase the power of legs experimental group, in conclusión states that no significant influence on theParkour training program to improve the power of legs in the group"Urban Ninjas Armenia".